The Constructivist Approach in the Implementation of MBKM for Higher Education in the Society 5.0 Era - Musyrifah, Farida; Rouzi, Kana Safrina; Fathurrohman, Rizal; Saryanto, Saryanto; Husen Ismail, Faisal; Andaryati, Erni (Universitas Muhammadiyah Surakarta, 2025)
The Merdeka Belajar–Kampus Merdeka (MBKM) program, launched by Indonesia’s Ministry of Education and Culture, seeks to improve the quality and relevance of higher education by granting students greater autonomy and learning flexibility. In the era of Society 5.0, where human and technological collaboration is essential, MBKM aligns with the constructivist philosophy that emphasizes active participation, collaboration, and reflection in constructing knowledge. This study employs a literature review approach within a constructivist philosophical framework, analyzing academic publications, policy documents, and empirical studies from 2020 to 2025 to explore how MBKM facilitates contextual, adaptive, and student-centered learning. The findings indicate that MBKM strengthens experiential and project-based learning by promoting collaboration among students, lecturers, and communities through internships and interdisciplinary projects. These practices enable learners to connect theory with real-world experiences, enhance critical and reflective thinking, and develop adaptive, creative, and resilient competencies. Viewed through a constructivist lens, MBKM represents a transformative educational innovation that bridges academic theory with societal application. It supports learner autonomy and cultivates holistic competencies necessary for the Society 5.0 era, preparing graduates to face global challenges with resilience, innovation, and a lifelong learning mindset. Overall, MBKM serves as a strategic model for advancing higher education that is contextual, adaptive, and responsive to the dynamic demands of the digital and technological age.